Ethical implications of digitised medical and biometric data - Siew, Siang-Ting; R., Mohd-Nor; S., Swartzman; Terrin, Lim (2010)
In this paper, ethical implications of data collection, use and retention of medical and biometric data in biometrics and medical applications are identified. These implications are discussed in the context of five main ethical rinciplesprivacy, confidentiality, security, property and ownership, and reliability and trustworthiness. In addition, to illustrate unethical uses of medical and biometric data, cases of misuse are described. Our research contributes to the European UnionГs FP7 ETHIcAL project, which aims to promote international...